Mesenchymal stem cells regulate epithelial–mesenchymal transition and tumor progression of pancreatic cancer cells. Issue 2 (11th January 2013) - Kabashima‐Niibe, Ayano; Higuchi, Hajime; Takaishi, Hiromasa; Masugi, Yohei; Matsuzaki, Yumi; Mabuchi, Yo; Funakoshi, Shinsuke; Adachi, Masayuki; Hamamoto, Yasuo; Kawachi, Shigeyuki; Aiura, Koichi; Kitagawa, Yuko; et al.
<x xml:space="preserve">Abstract</x> Cancer‐associated fibroblasts contribute to cancer progression that is caused by epithelial–mesenchymal transition (EMT). Recently, mesenchymal stem cells (MSCs) were found to be the major candidate involved in the development of tumor‐promoting cancer stroma. Here we report that α‐smooth muscle actin‐positive myofibroblast‐like cells originating from MSCs contribute to inducing EMT in side population cells of pancreatic cancer. More importantly, MSC‐derived myofibroblasts function to maintain tumor‐initiating stem cell‐like characteristics, including augmenting expression levels of various stemness‐associated genes, enhancing sphere‐ forming activity, promoting tumor formation in a mouse xenograft model, and showing resistance to anticancer drugs. Furthermore, both γ‐secretase inhibitor and siRNA directed against Jagged‐1 attenuated MSC‐associated E‐cadherin suppression and sphere formation in pancreatic cancer side population cells. Thus, our results suggest that MSC‐derived myofibroblasts play important roles in regulating EMT and tumor‐initiating stem cell‐like properties of pancreatic cancer cells through an intermediating Notch signal.